Decomposition and decoupling analysis of carbon emissions from economic growth: A case study of Pakistan - Sher Khan; Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Climate change induced by the growth of carbon dioxide emissions has become a global concern. Therefore, it's necessary to pinpoint the factors thatdrive carbon emissions to provide suitable mitigation policies. This study uses Taipo Decoupling Index and Log MeanDivisa Index (LMDI) decomposition techniques to examine Pakistan's decoupling status between environmental impact and economic growth and to analyzedriving forces of carbon emissions over a time span of 1990-2014.The outcome suggests that Pakistan has experienced four decoupling statuses, where the most prominent is the expensive negative decoupling status. Furthermore, energy intensity and carbon intensity usually encouraged decoupling, while economic growth and energy structure restricted it. The population has a neutral effect on decoupling. The decomposition results demonstrated that population, energy structure, and economic growth significantly contributed to carbon emissions. While, energy and carbon intensity help in curbing carbon emissions. Thisstudy provides useful insights to mitigation carbon emissions. Besides, it also helps in promoting sustainable economic growth.
Keywords: 330; log mean divisia index; decomposition; CO2; decoupling elasticity analysis; Pakistan